Thromboembolic Complications after Bariatric and Metabolic Surgery: A Single-Center Experience, Two Case Reports and a Literature Review - Juodeikis, Žygimantas; Brimas, Gintautas (Acta medica Lituanica, 2024)
Background: Bariatric and metabolic surgery has emerged as an effective intervention for morbid obesity, offering substantial and sustained weight loss along with improvements in various comorbidities. Among the diverse spectrum of potential postoperative complications, thromboembolic events have garnered increasing attention due to their significant morbidity and mortality.The aim of this study is to present a single-center experience of thromboembolic complications following bariatric and metabolic surgery. Additionally, we present two distinctive cases, highlighting the clinical manifestations, diagnostic challenges, and therapeutic interventions associated with postoperative thromboembolism.Materials and Methods: We retrospectively reviewed data from patients with obesity who underwent various bariatric and metabolic operations at Republican Vilnius University Hospital from January 2018 to February 2024. All patients, regardless of the type of operation performed, were included. Two patients with thromboembolic complications are presented as illustrative cases.Results: A total of 633 patients were included in the analysis: 278 underwent laparoscopic adjustable gastric banding, 345 underwent sleeve gastrectomies, and 10 underwent gastric bypasses. Thromboembolic complications occurred in only two patients, with one developing portal vein thrombosis and the other developing pulmonary embolism.Conclusions: This single-center experience emphasizes the unpredictable nature of thromboembolic events in postbariatric surgery patients and highlights the critical role of vigilant monitoring, early detection, and individualized therapeutic interventions. Continued research efforts are warranted to refine risk stratification, enhance preventive measures, and improve overall patient outcomes in the landscape of bariatric surgery.